How to design and evaluate research in education - Fraenkel, Jack R. 1932-; Hyun, Helen H; Wallen, Norman E (McGraw Hill LLC, 2023)
How to Design and Evaluate Research in Education is directed to students taking their first course in educational research. Because this field continues to grow so rapidly with regard to both the knowledge it contains and the methodologies it employs, the authors of any introductory text are forced to carefully define their goals as a first step in deciding what to include in their book. In our case, we continually kept three main goals in mind. We wanted to produce a text that would: 1. Provide students with the basic information needed to understand the research process, from idea formulation through data analysis and interpretation. 2. Enable students to use this knowledge to design their own research on a topic of personal interest. 3. Allow students to read and understand educational research literature. The first two goals are intended to satisfy the needs of those students who must plan and carry out a research project as part of their course requirements. The third goal is aimed at students whose course requirements include learning how to read and understand the research of others. Many instructors, ourselves included, build all three goals into their courses, since each one seems to reinforce the others. It is hard to read and fully comprehed the research of others if you have not yourself gone through the process of designing and evaluating a research project"--